Experience-Dependent Development and Maintenance of Binocular Neurons in the Mouse Visual Cortex - Jenks, Kyle R. (Cell Rep, 2020)
The development of neuronal circuits requires both hard-wired gene expression and experience-dependent plasticity. Sensory processing, such as binocular vision, is especially sensitive to perturbations of experience. We investigated the experience-dependent development of the binocular visual cortex at single-cell resolution by using two-photon calcium imaging in awake mice. At eye-opening, the majority of visually responsive neurons are monocular. Binocular neurons emerge later with visual experience and acquire distinct visual response properties. Surprisingly, rather than mirroring the effects of visual deprivation, mice that lack the plasticity gene Arc show increased numbers of binocular neurons and a shift in ocular dominance during development. Strikingly, acutely removing Arc in the adult binocular visual cortex also increases the number of binocular neurons, suggesting that the maintenance of binocular circuits requires ongoing plasticity. Thus, experience-dependent plasticity is critical for the development and maintenance of circuits required to process binocular vision.